The Types and Motives of Maxim Infringement in Agatha Christie’s Murder on The Orient Express Novel (Pragmatic Approach) - darmawan, Adhitya; Nada Humaida Rohmah (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2024)
This study performs a pragmatic analysis of Agatha Christie’s